Profitabilitas, Leverage Dan Manajemen Pajak Perusahaan Manufaktur Sektor Pertambangan - Meidy Santje Selvy Kantohe; Tinneke Sumual; Natalia Maria Umar (Universitas PGRI Madiun, 2023)
Tax is a source of state revenue that supports the implementation of development and improves people's welfare. The company is one of the taxpayers who has the obligation to pay taxes in accordance with statutory provisions. However, tax for companies is a burden that will reduce net income so that many companies take tax management actions to reduce their tax obligations. Tax management carried out by the company can minimize the tax burden that must be paid by the company. This study aims to determine the effect of profitability and leverage on tax management in mining sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses secondary data obtained through the company's annual financial reports. The sample selection method in this study used a purposive sampling method and the sample for this study was 69 samples with observations for 3 years. Data analysis using panel data regression method. The results of this study indicate that profitability has a negative effect on tax management. The higher the profitability, the lower the tax management. While leverage has no effect on tax management. Keywords: Profitability; Leverage ;Tax Management.